A better pencil : readers, writers, and the digital revolution - Baron, Dennis E. (Oxford University Press, 2009)
Computers, now the writer's tool of choice, are still blamed by skeptics for a variety of ills, from speeding writing up to the point of recklessness, to complicating or trivializing the writing process, to destroying the English language itself. A Better Pencil puts our complex, still-evolving hate-love relationship with computers and the internet into perspective, describing how the digital revolution influences our reading and writing practices, and how the latest technologies differ from what came before. The book explores our use of computers as writing tools in light of the history of co.